EFFICACY OF ADALIMUMAB IN A PATIENT WITH JUVENILE IDIOPATHIC ARTHRITIS AND UVEITIS - L. A. Galstyan; E. S. Zholobova; O. S. Razvadovskaya; A. V. Bunin; A. V. Starikova ("Paediatrician" Publishers LLC, 2012)
A history case of a female patient with juvenile idiopathic arthritis, resistant to steroids and methotrexate and secondary resistance to infliximab, is represented in this article. Switching to another tumor necrosis factor-alpha inhibitor - adalimumab - led to induction of steady remission of joint syndrome and uveitis, steroids, methotrexate and non-steroidal anti-inflammatory drugs withdrawal.